Case report: Unveiling a less severe congenital nephrotic syndrome in a Rapa Nui patient with a NPHS1 Maori founder variant - Krall, Paola; Rojo, Angélica; Plaza, Anita; Canals, Sofia; Ceballos, María Luisa; Cano, Francisco; Guerrero, José Luis (Frontiers in Nephrology, 2024)
BackgroundCongenital nephrotic syndrome (CNS) is a severe kidney disorder characterized by edema, massive proteinuria, and hypoalbuminemia that manifests in utero or within three months after birth. CNS affects 1-3 per 100,000 children, primarily associated with genetic variants and occasionally with infections. Genetic analysis is the first-line method for diagnosis. The most common founder variants have been identified in European populations, often resulting in end-stage kidney disease by 1-2 years of age.Case-diagnosis/treatmentA female full-term neonate, without prenatal signs of kidney disease, was admitted to Rapa Nui (Eastern Island) Hospital at the age of 2 months due to bronchial obstruction. She presented fever, oliguria, edema, urine protein-to-creatinine ratio (UPCR) 433.33, and hypoalbuminemia (0.9 g/dL). She was transferred to a mainland Chilean hospital following CNS diagnosis. Viral screening detected cytomegalovirus (CMV) positivity in both blood and urine. A kidney biopsy revealed interstitial nephritis and diffuse podocyte damage and the tissue PCR resulted negative for CMV. Interviews with the parents revealed consanguinity, suggestive of hereditary CNS. Genetic analysis identified the Maori founder variant, NPHS1 c.2131C>A (p.R711S), in homozygosis. The patient received albumin infusions and antiviral therapy, being discharged when she was 5 months old, with improved laboratory parameters evidenced by UPCR 28.55, albumin 2.5 g/dL, and cholesterol 190 mg/dL. Subsequent clinical monitoring was conducted through virtual and in-person consultations. At her last follow-up at 4 years 2 months old, she presented UPCR 16.1, albumin 3.3 g/dl and cholesterol 220 mg/dL, maintaining normal kidney function and adequate growth.ConclusionsTo our knowledge, this represents the first case of CNS in Chile carrying a NPHS1 variant associated with prolonged kidney survival. As described in the Maori population, the patient exhibited a less severe clinical course compared to classical NPHS1 patients. Genetic testing for the Maori founder variant in CNS patients related to the New Zealand population, could impact management decisions and potentially prevent the need for nephrectomies.